Viral Marketing, Brand Image, and the FOMO Effect: A Behavioral Economics Study on Kazamarts Indonesia - Abdillah, Muhammad Husein; Jumai, Jumai; Purwanto, Edy; Firdaus, Firdaus (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to examine the role of Fear of Missing Out (FOMO) in moderating the influence of viral marketing and brand image on consumer purchase decisions of Kazamarts Indonesia's fashion products. A total of 100 respondents were selected using purposive sampling, targeting individuals who have engaged with Kazamarts' online marketing and have made or considered making a purchase. Data were collected using a Likert scale questionnaire ranging from 1 (strongly disagree) to 5 (strongly agree). The analysis was conducted using Partial Least Squares (PLS) to test the proposed structural model. The findings reveal that both viral marketing and brand image significantly influence FOMO and consumer purchase decisions. Furthermore, FOMO was found to moderate the relationship between viral marketing and purchase decisions, strengthening the effect, while its moderating role on brand image was less significant. These results highlight the importance of emotional triggers like FOMO in digital marketing strategies for fashion brands targeting online consumers.